PENGARUH LAYANAN BIMBINGAN KELOMPOK DALAM MENGURANGI PERILAKU BULLYING MELALUI MEDIA SOSIAL - Jamiatul Ilmi; Wahidah Fitriani; Deni Rahman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study discusses how to reduce bullying behavior on social media through group guidance services. The aim of the study was to see whether or not guidance services were significant in reducing student bullying behavior. The research method used was an experimental method, namely research that aimed to see changes in students' learning attitudes with guidance services. group. The type of design used in this study is a Quasi-Experimental design with a one group pretest-posttest design. Topics discussed in group counseling services. The results of the study showed that there was a significant change in bullying behavior on social media.